Form IV: From Ruyer's Psychobiology to Deleuze and Guattari's Socius. Issue 4 (November 2017) - Roffe, Jon
Abstract : From the point of view of the philosophy of Gilles Deleuze, Raymond Ruyer's work appears to bear out two distinct tendencies of unequal appeal. On the one hand, Ruyer appears to be an anti-Aristotelian thinker of formation, rejecting any hylomorphic account of the production of reality. However, and notably despite his serious commitment to the work of the sciences of his day, he remains wedded to the ultimately conservative Leibnizian principle of closure. Nowhere is this dichotomy more striking than in his account of human society. The aim of this paper is to show how his positive account of form(ation) finds a significant and convincing extension in Deleuze and Guattari's notion of social surface or socius in Anti-Oedipus .